Conceptual Design of an Unmanned Fixed-Wing Aerial Vehicle Based on Alternative Energy - Alan G. Escobar-Ruiz; Omar Lopez-Botello; Luis Reyes-Osorio; Patricia Zambrano-Robledo; Luis Amezquita-Brooks; Octavio Garcia-Salazar (International Journal of Aerospace Engineering)
This paper focuses on the aerodynamics and design of an unmanned aerial vehicle (UAV) based on solar cells as a main power source. The procedure includes three phases: the conceptual design, preliminary design, and a computational fluid dynamics analysis of the vehicle. One of the main disadvantages of an electric UAV is the flight time; in this sense, the challenge is to create an aerodynamic design that can increase the endurance of the UAV. In this research, the flight mission starts with the attempt of the vehicle design to get at the maximum altitude; then, the UAV starts to glide and battery charge recovery is achieved due to the solar cells. A conceptual design is used, and the aerodynamic analysis is focused on a UAV as a gliding vehicle, with the calculations starting with the estimation of weight and aerodynamics and finishing this stage with the best glide angle. In fact, the aerodynamic analysis is obtained for a preliminary design; this step involves the wing, fuselage, and empennage of the UAV. In order to achieve the preliminary design, an estimation of aerodynamic coefficients, along with computational fluid dynamics analysis, is performed.